Development of hepatic steatosis in normal and veinous livers of overfed female mule ducks - S. Trehiou; E. Atallah; V. Alquier-Bacquie; F. Lasserre; J. Arroyo; C. Molette; H. Remignon (Animal)
Following the various recent avian influenza crises, the shortage of male mule ducklings has led to the use of females, although these are not normally used mainly because of defects in the presentation of the final product. The aim of this study was to examine the evolution of hepatic steatosis induced by overfeeding in female mule ducks with or without a visible network of veins on the surface of lean or fatty livers. The overall evolution of hepatic steatosis (weight gain, gross biochemical composition) was strikingly similar in both types of liver. Histological observations confirm that in both types of livers, there is a steady increase in the accumulation of lipid droplets in hepatocytes throughout the period of overfeeding. At the same time, other parameters (fibrogenesis, measured by the accumulation of hydroxyproline; oxidative status, measured by the activities of the enzymes superoxide dismutase and catalase; contents of reduced and oxidised glutathione and level of hypoxia, measured with Hypoxia 1 and 2 Induced Factors) are also altered similarly in all samples. Nor did the overall activities of genes belonging to different metabolic pathways reveal any major differences when normal and veinous livers were compared. In conclusion, hepatic steatosis induced by overfeeding developed under very similar conditions in the normal and veinous livers of female mule ducks. However, these visible anatomical differences degrade the visual quality of the final product and make veinous livers less attractive to processors and consumers.